Analysis of Teacher Difficulties in Implementing Science Learning Based on Ethnoscience for Class IV SDN Kedungpane 02 - Kediri, Shafira Ratu Sekartaji Putri; Wulandari, Ritanur Aliya; Ardhani, Syafira Prameswari; Putri, Najwa Rheina; Amriya, Yassirli; Sutikno, Putri Yanuarita (Jurnal Riset Ilmu Pendidikan, 2025)
Ethnoscience learning in basic education is a culture-based approach that aims to instil a love for local and national culture in accordance with the material in the Merdeka Curriculum. Basically, using ethnoscience learning will make it easier for teachers to teach science that can be related to local culture. This study uses a qualitative method with research at Kedungpane 02 Elementary School which explores various problems regarding ethnoscience learning using catapults in grade 4 SD. Based on the results of the study, it shows that teachers experience various difficulties in learning ethnoscience in class IV students at SDN Kedungpane 02, especially in conditioning students when learning ethnoscience outside the classroom.